Alta frequência de sororreatividade contra o sorogroupo Tarassovi na região do Triângulo Mineiro, estado de Minas Gerais, Brasil - Soares, P. M.; Gomes, D. O.; Soares, M. M.; Silva, D. M.; Cuccato, L. P.; Ciuffa, A. Z.; Rezende, L. M.; Paiva, V. V.; Buiatte, A. B. G.; Queiroz, C. L.; Lima, A. M. C. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Leptospirosis is an important zoonosis that affects wild and domestic animals, mainly cattle. The serogroup Sejroe is the most frequent in cattle and is associated with reproductive alterations, causing economic losses to milk and meat production. However, the occurrence of serogroup Tarassovi reactivity in cattle is not enough investigated. Until now reactivity to this serovar was mainly found in wild and domesticated swine. Thus, due to the possibility of close contact between cattle and wild animal. species, serological investigations must be performed to clarify this assumption.